Kajian Kelayakan dan Pengembangan Lahan Budidaya Kepiting Bakau (Scylla spp) di Desa Kabupaten Minahasa Utara - M, Mardiana; Mingkid, Winda; Sinjal, Hengky (e-Journal BUDIDAYA PERAIRAN, 2015)
This research intended to evaluate the area suitability of  Scylla spp at Likupang II Village, North Minahasa. The research was done descriptively by observing water quality, area availability. SWOT analysis was used to determine the development strategy.   Data were collected by interview, observation and questionnaire.  Research result showed that the potential of Likupang II Village was suitable for Scylla spp culture.  SWOT analysis showed internal factors affected the development of Scylla spp culture.  The strength were location, water quality, government support; the weakness were seed availability, opportunity, government policy and treating were season and safety.   Keywords : Scylla spp, SWOT analysis, , Likupang II, area suitability